Dynamics of Lintner's model in the dividend payment process of Nigerian banks - Odunayo Magret Olarewaju; Mabutho Sibanda; Stephen Oseko Migiro (SPOUDAI - Journal of Economics and Business, 2017)
This study examines the dynamics of Lintner's model using bank-specific panel data from 15 commercial banks listed on the Nigerian Stock Exchange, using the newly introduced dynamic Panel-Auto Regressive Distributed Lag technique for the Period 2006Q01 to 2015Q04. The study findings from the long-run estimates reveal that Lintner's model holds well, but with a negative effect of profitability on dividend payout of banks in Nigeria during the period in question. The findings further reveal evidence of a co-integrating relationship among past year dividend, profitability, capital adequacy and taxation, and with evidence of unidirectional short-run causality among the variables used to test Lintner's model and the dividend payout ratio. Based on these findings, this study concludes that dividend process in Nigeria support the information-content-hypothesis' argument by strict adherence to Lintner's model in Nigerian banking sector.
Keywords: G11; G21; G35; 330; dynamics of Lintner's model; Nigerian banking sector; dividend policy; Panel-ARDL